2020
DOI: 10.3324/haematol.2019.242727
|View full text |Cite
|
Sign up to set email alerts
|

Sec22b determines Weibel-Palade body length by controlling anterograde ER-Golgi transport

Abstract: Sec22b determines Weibel-Palade body length by controlling anterograde ER-Golgi transport.Abstract Von Willebrand factor (VWF) is a multimeric hemostatic protein that is synthesized in endothelial cells, where it is stored for secretion in elongated secretory organelles, so-called Weibel-Palade bodies (WPBs). Hemostatic activity of VWF is strongly tied to WPB length, but how endothelial cells control the dimensions of their WPBs is unclear. In this study we used a targeted shRNA screen to identify the longin-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Consequently, the generated model of D1D2DʹD3 was used to dock two proteins Sec24 and ARF1, for whom limited evidence exists for their role in anterograde transport of VWF (Karampini et al, 2021; Lopes‐da‐Silva et al, 2019). The atomic structure of ARF1 and Sec24 was extracted from the PDB ID: 2J59 with resolution: 2.1 Å and PDB ID: 3EFO with resolution: 2.7 Å, respectively (Mancias & Goldberg, 2008; Ménétrey et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the generated model of D1D2DʹD3 was used to dock two proteins Sec24 and ARF1, for whom limited evidence exists for their role in anterograde transport of VWF (Karampini et al, 2021; Lopes‐da‐Silva et al, 2019). The atomic structure of ARF1 and Sec24 was extracted from the PDB ID: 2J59 with resolution: 2.1 Å and PDB ID: 3EFO with resolution: 2.7 Å, respectively (Mancias & Goldberg, 2008; Ménétrey et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In eukaryotic cells, trafficking of newly synthesized proteins is organized by COPI‐ and COPII‐coated vesicles that contribute to the recruitment of proteins and ER‐Golgi transport, as well as ER exit quality control (QC) by excluding misfolded cargos from vesicles (Duden, 2003; Ellgaard et al, 1999; Karampini et al, 2021; Peotter et al, 2019). Current studies point to two major protein complexes modulating VWF exit from ER, ARF (ADP‐ribosylation factors) 1‐GEF and Sec23/24‐Sec22b, which have a role in selecting and recruitment of the cargo proteins in COPI and COPII complexes, respectively (Duden, 2003; Karampini et al, 2021; Lopes‐da‐Silva et al, 2019; Peotter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…67 Downregulation of Sec22b affects the rate of ER/Golgi transport of VWF and other proteins, which consequently affects the Golgi morphology and results in the formation of short and stubby WPBs, probably due to Golgi fragmentation. 66,68 Additionally, we and others have shown that Sec22b is paired with STX5 (syntaxin-5) as part of the ER-Golgi SNARE machinery, and depletion of STX5 in endothelial cells strongly affects WPB formation. 69,70 Depletion of STX5 in endothelial cells leads to decreased intracellular VWF storage levels and extensive Golgi dispersal, which results in the formation of shorter and rounder WPBs.…”
Section: Biogenesis and Maturation Of Wpb In Endothelial Cells Vwf Mamentioning
confidence: 88%
“…64 Similar results with ER retention of VWF and formation of abnormal WPBs have been recently shown in Sec22b knockdown endothelial cells. 66 Sec22b is a SNARE protein that regulates the fusion of COPII (coat protein complex II)-coated ER-exiting vesicles. 67 Downregulation of Sec22b affects the rate of ER/Golgi transport of VWF and other proteins, which consequently affects the Golgi morphology and results in the formation of short and stubby WPBs, probably due to Golgi fragmentation.…”
Section: Biogenesis and Maturation Of Wpb In Endothelial Cells Vwf Mamentioning
confidence: 99%
See 1 more Smart Citation